Knowledge, attitudes, perceptions, and misconceptions among vitiligo patients in Southwest, Saudi Arabia - Alfahaad, Hamad; Alghamdi, Saleh Mesfer; Alsaiari, Soliman; Alfarwan, Wadha; Farhan, Anwar Ali; Alfataih, Mahdi; Al Ameer, Mohammed; Al Hadi, Enas (Journal of Pakistan Association of Dermatologists, 2024)
Objectives: The study assesses the degree of knowledge possessed by patients with vitiligo in southwest Saudi Arabia regarding the diseaseâ€™s etiology, diagnosis, management, and prognosis. Additionally, the study identifies factors associated with patientsâ€™ knowledge about the disease. Methods: The study administered a questionnaire in Arabic and English languages to measure the patients’ knowledge about the causes of vitiligo, associated conditions, and available treatment options. The questionnaire was distributed among 293 patients diagnosed with vitiligo in the dermatology outpatient clinics at Khamis Mushayt General Hospital and King Khalid Hospital in Najran during the study period. Data analysis was conducted using Ï‡2 test for categorical variables. Results: 293 patients were recruited in this study. Of these, 124 (42.3%) were male, and 169 (57.7%) were female. Most patients were young, falling within the age group of 22â€“39 years. Approximately 156 (53.3%) of the patients possessed no awareness regarding causes of vitiligo. Only 52 (17.7%) patients demonstrated good knowledge related to vitiligo, while 241 (82.3%) had poor knowledge. Stress and fear were considered causative or aggravating factors by 68 (23.2%) patients. Additionally, only 138 (47.1%) patients were aware that the loss of pigment cells contributes to vitiligo. Herbal compounds were considered effective treatment agents by 56 (19.1%) patients. In addition, 211 (72%) patients were aware of vitiligo treatment with topical steroids, but 82 (28%) responded that they did not know about these treatment modalities. Conclusion: Erroneous beliefs, misconceptions, and myths surrounding vitiligo were uncovered in this study. These misconceptions often lead to delayed medical advice-seeking and poor adherence to medication. To address this, health education programs should be implemented by health authorities, focusing on mass disease education.